Stevioside mitigates metabolic dysregulation in offspring induced by maternal high-fat diet: the role of gut microbiota-driven thermogenesis - Jin Ye; Renjie Shi; Xiaoning Wu; Hua Fan; Yapei Zhao; Xinyun Hu; Lulu Wang; Xiaowei Bo; Dongning Li; Yunshu Ge; Danna Wang; Bing Xia; et al. (Gut Microbes)
Maternal obesity poses a significant threat to the metabolic profiles of offspring. Microorganisms acquired from the mother early in life critically affect the host’s metabolic functions. Natural non-nutritive sweeteners, particularly stevioside (STV), play a crucial role in reducing obesity and affecting gut microbiota composition. Based on this, we hypothesized that maternal STV supplementation could improve the health of mothers and offspring by altering their gut microbiota. Our study found that maternal STV supplementation reduced obesity during pregnancy, decreased abnormal lipid accumulation in offspring mice caused by maternal obesity, and modified the gut microbiota of both dams and offspring, notably increasing the abundance of Lactobacillus apodemi (L. apodemi). Co-housing and fecal microbiota transplant experiments confirmed that gut microbiota mediated the effects of STV on metabolic disorders. Furthermore, treatment with L. apodemi alone replicated the beneficial effects of STV, which were associated with increased thermogenesis. In summary, maternal STV supplementation could alleviate lipid metabolic disorders in offspring by enhancing L. apodemi levels and promoting thermogenic activity, potentially involving changes in bile acid metabolism pathways.